Negative Transfer Effects on L2 Word Order Processing - Erdocia, Kepa; Laka, Itziar (Frontiers in Psychology, 2018)
Does L1 word order affect the processing of non-canonical but grammatical syntactic structures in L2 comprehension? In the present study, we test whether L1-Spanish speakers of L2-Basque process Subject-Verb-Object and Object-Verb-Subject non-canonical word order sentences of Basque in the same way as Basque native speakers. Crucially, while OVS orders are non-canonical in both Spanish and Basque, SVO is non-canonical in Basque but is the canonical word order in Spanish. Our electrophysiological results showed that the characteristics of L1 affect the processing of the L2 even at highly proficient and early-acquired bilingual populations. Specifically, in the non-native group, we observed a LAN-like component when comparing S and O at sentence initial position and a P600 when comparing those elements at sentence final position. Those results are similar of those reported by Casado et al. (2005) for native speakers of Spanish indicating that L2-Basque speakers rely in their L1-Spanish when processing SVO-OVS word order sentences. Our results favored the Competition Model (MacWhinney 1997).